Characterization of mesenchymal stromal cells physical properties using acoustic radiation force - Bellebon, Ludovic; Sugier, Hugo R.; Larghero, Jérôme; Peltzer, Juliette; Martinaud, Christophe; Hoyos, Mauricio; Aider, Jean-Luc (Frontiers in Physics, 2022)
Microfluidics-based technologies are emerging solutions towards cell separation process. They rely on various physical principles, such as dielectrophoretic force, hydrodynamic force, and acoustic force. In order to take advantage of these approaches for cell sorting, it is crucial to characterize cell biophysical properties, i.e. size, density, compressibility or acoustic contrast factor in the case of acoustophoresis. Various techniques exist to measure those features, including acoustofluidics methods. However, previously described approaches do not allow the determination of all the physical parameters of a given cell. For this study a 330 μm deep acoustic cavity has been designed, together with an optical technique, to measure the size, acoustic contrast factor and density of cells to finally determine their compressibility. A defocusing technique is used to assess the velocity of sedimentation and acoustic focusing of individual cells which can lead to their physical properties using the analytic expression of the Acoustic Radiation Force. This method is used to investigate the evolution of the biophysical properties of mesenchymal stromal cells (MSCs), isolated from two different tissues from different donors, from one passage to the other. Our results highlighted an important heterogeneity of acoustic contrast factor and compressibility among cells from a same donor but also inter-donor. Nevertheless, from passage to passage, the acoustic contrast factor and compressibility of MSCs converge and homogenize at the fourth passage. On the other hand, the density of MSCs remains homogenous from passage to passage and between different donors. Using this technique, it was possible to successfully assess the different biophysical properties of mesenchymal stromal cells using a single setup based on acoustic levitation. The results confirm the necessity to use such a technique to measure the cells properties. It also demonstrates the large heterogeneity of donor/patient-derived cells, in contrast with cultured cells whose properties homogenize during the successive cultures. As a consequence, cell separation processes will be more complex for patient/donor derived cells than for cultured cells.